PEGARUH SUBSTRAT BERBEDA TERHADAP PENEMPELAN TELUR PADA PEMIJAHAN IKAN BADUT (Amphiprion Ocellaris) - Velita Oktavianti; Nunik Cokrowati; Bagus Dwi Hari Setyono (Universitas Mataram, 2021)
In spawning clown fish it takes a treatment on the manipulation of the place of origin of clown fish to spawn in cultivation containers. Tile and ceramic substrates are suitable for the attachment of clownfish larvae because the texture of the two substrates is hard, this indicates that the type of hard substrate will be able to be made a living place for clownfish, because the properties of clown fish must grow and develop in hard substrates. This research was conducted with the aim of studying differences in the survival of clown fish larvae on different substrates. This research was conducted for 45 days, starting from 1 September to 15 October 2021 at the Lombok Marine Cultivation Fisheries Center (BPBLL). The method used in this research is to use an experimental method with a completely randomized design (CRD) pattern with four treatments with 3 replications, namely P1 (ceramic substrate), P2 (tile substrate), P3 (paralon substrate), P4 (pottery substrate). . The test animals used in this study were male and female clown fish (Amphiprion ocellaris) aged between 4-5 years. Based on the research that has been done, there are fertilization results P1 = 88.67%, P2 = 94.17%, P3 = 83.83%, P4 = 78.67%. While the results of hatchability P1 = 88.67%, P2 = 94.17%, P3 = 83.83%, P4 = 78.67%. And the results of survival were P1 = 82.15%, P2 = 82.84%, P3 = 80.94%, P4 = 80.11%. The conclusion of this study was that the use of ceramic, tile, paralon, and earthenware substrates had no effect on fertilization and hatchability of clown fish eggs. The survival of clown fish has a significant effect on the use of substrate in spawning clown fish.